1993
DOI: 10.1002/gj.3350280315
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characteristics of granitoids along the western margin of the Central Anatolian Crystalline Complex and their tectonic implications

Abstract: The closely related assemblage of igneous and metamorphic rocks that lie within a triangular area approximately bounded by the Tuzgolu Fault, the EcemiS Fault and the Izmir-Ankara-Erzincan Suture and between the lines connecting Ankara, Sivas and Nigde is called the Central Anatolian Crystalline Complex (CACC). The granitoids cropping out within the CACC can be divided areally into three groups: (1) a large number of individual small plutons which form an arcuate set and curve from NE-SW to NW-SE and extend fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 6 publications
0
42
0
4
Order By: Relevance
“…1b). Both granitoids are considered to be cogenetic with similar granitoids from Central Anatolia Kuscu et al 2001), whose tectonic settings are suggested as collisional/post-collisional (Goncuoglu and Tureli 1994;Akiman et al 1993;Erler and Goncuoglu 1996;Boztug 1998Boztug , 2000Aydin et al 1998;Yaliniz et al 1999) and/or magmatic arc (Gorur et al 1984;Kocak 1993;Kocak and Leake 1994;Kadioglu and Gulec 1996).…”
Section: Geological Setting and Field Characteristicsmentioning
confidence: 95%
“…1b). Both granitoids are considered to be cogenetic with similar granitoids from Central Anatolia Kuscu et al 2001), whose tectonic settings are suggested as collisional/post-collisional (Goncuoglu and Tureli 1994;Akiman et al 1993;Erler and Goncuoglu 1996;Boztug 1998Boztug , 2000Aydin et al 1998;Yaliniz et al 1999) and/or magmatic arc (Gorur et al 1984;Kocak 1993;Kocak and Leake 1994;Kadioglu and Gulec 1996).…”
Section: Geological Setting and Field Characteristicsmentioning
confidence: 95%
“…They lie within the metaluminous to peraluminous and also the I-type granite field (Figure 9a). The majority of the granitoid components from the CACC plutons show a calcalkaline affinity, with a metaluminous to peraluminous character, and they mainly plot within the volcanic arc and collisional granite field on the trace element discrimination diagrams (Akıman et al, 1993;Kuşcu et al, 2002;Kadıoğlu et al, 2003 and references therein;İlbeyli et al, 2009). Metaluminous to peraluminous I-type granitoids are interpreted to have originated in a volcanic arc setting (Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The post-collisional granitoids intrude the metamorphic rocks and the ophiolites during and after the southward obduction of the ophiolitic rocks from Neotethys onto the Tauride±Anatolide Block during the Late Cretaceous Göncüog AE lu et al 1991;Akõman et al 1993), but before the Late Maastrichtian (Yalõnõz et al 1996). The isotopic data on the age of granitoids are scarce and range from 54 to 110 14 Ma (Ayan 1963;Ataman 1972;Göncüog AE lu 1986;Güleç 1994;Yalõnõz et al 1999).…”
Section: þAmlõca Metamorphicsmentioning
confidence: 96%